Deep imaging with low-cost photoacoustic tomography system with pulsed diode laser - Pramanik, Manojit (2015)
Optical imaging beyond a few mm inside biological tissue is a challenging task due to the light scattering inside the biological tissue. Photoacoustic tomography (PAT) breaks this depth limit of optical imaging by combining light and sound. Over the last few years PAT has emerged as a viable deep tissue imaging modality and created lot of attention to the medical imaging community. However, the cost, size and time consuming image acquisition of the PAT system is deterrent to its translation to real clinical applications. So, there is a need for inexpensive, compact, simple, fast PAT imaging system for easy adoption by the clinical practitioners. Nanosecond pulsed laser diodes could help to bring down the cost, size and image acquisition time and make PAT attractive for deep tissue imaging of optical contrast with high resolution. In this work, we present our findings on using a low-cost pulsed diode laser for deep tissue imaging with photoacoustics. The PAT system was tested on tissue phantoms to verify its potential imaging depth demonstration. Up to 3 cm deep inside chicken breast tissue we were able to see photoacoustic signals and up to 2 cm deep we were able to image successfully.